2021
DOI: 10.3390/ijerph18179388
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Noise Exposure and Incidence of High Fasting Blood Glucose: A 3-Year, Multicenter, Retrospective Study

Abstract: The role of hazardous occupational noise exposure on the development of prediabetes is not well researched. We aimed to elucidate exposure to hazardous occupational noise as an independent risk factor for high fasting blood glucose (FBG). Participants exposed/non-exposed to occupational noise were recruited from the Common Data Model cohorts of 2013/2014 from two centers and were followed-up for 3 years. Multivariate time-dependent Cox proportional hazard models were used to estimate hazard ratios (HRs) and 95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The workers exposed to hazardous noise may experience multiple adverse health outcomes, including hearing difficulty, hypertension, high fasting blood glucose, depression, dementia, fall, increased hospitalization, and health care costs. 5,9,25 -28 The results of this study showed that the risk of noise exposure levels equal to or exceeding 85 dB(A) in Beijing was lower than the national level, which was reported by Chinese Center for Disease Control and Prevention in 2021, the proportions of 9926 small enterprises and 7116 micro enterprises with noise exposure levels equal or exceeding 85 dB(A) were 24.00% and 30.11%, respectively. 16 But the situation of noise hazard prevention and control was severe.…”
Section: Discussionmentioning
confidence: 60%
“…The workers exposed to hazardous noise may experience multiple adverse health outcomes, including hearing difficulty, hypertension, high fasting blood glucose, depression, dementia, fall, increased hospitalization, and health care costs. 5,9,25 -28 The results of this study showed that the risk of noise exposure levels equal to or exceeding 85 dB(A) in Beijing was lower than the national level, which was reported by Chinese Center for Disease Control and Prevention in 2021, the proportions of 9926 small enterprises and 7116 micro enterprises with noise exposure levels equal or exceeding 85 dB(A) were 24.00% and 30.11%, respectively. 16 But the situation of noise hazard prevention and control was severe.…”
Section: Discussionmentioning
confidence: 60%
“…A retrospective cohort study of 43,858 Korean workers found that after adjusting for potential confounders, including age, sex, education, smoking, alcohol consumption, and physical activity, exposure to hazardous noise in the workplace (≥85 dB) was associated with an increased risk of hyperglycemia (Hazard Ratio [HR]: 1.28, 95% CI = 1.16–1.41) (Kim et al., 2021 ). Similarly, a cross‐sectional small‐scale observational study in Bulgaria reported that exposure to road traffic noise of 71–80 dB was associated with type 2 diabetes (OR: 4.49, 95% CI = 1.38–14.68) compared to the noise of 51–70 dB (Dzhambov & Dimitrova, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…As a physiological stressor, environmental noise activates the HPA axis and the sympathetic nervous system, known as the sympathetic‐adrenal‐medulla axis. These stress hormones can trigger counter‐regulatory hormones such as adrenaline and cortisol, which could be linked to the release of insulin resistance, resulting in increased food consumption and abdominal fat distribution (Kim et al., 2021 ). Furthermore, sleep deprivation and endocrine explosion due to noise exposure can affect adverse immune responses, control of stress hormones, and gastrointestinal function (Cai et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged exposure to noise at certain intensities has been linked to significant abnormalities in serum glucose, total cholesterol, triglycerides, high-density lipoprotein cholesterol (HDL-C), and low-density lipoprotein cholesterol (LDL-C) levels. [10] In research employing the Framingham cardiovascular disease risk model, noise energy was found to be positively correlated with the risk of cardiovascular disease [1] .…”
mentioning
confidence: 99%